Internalizing Religious Moderation through the Hidden Curriculum: A Case Study of an Indonesian Madrasah - Pramana Aji, Arif; Santoso, Budi; Andri Pramita, Roni; Artikasari Arifin, Liana; Anakotta, Raisa (Universitas Muhammadiyah Magelang, 2026)
Religious moderation has become a strategic priority in Islamic education, as madrasahs are expected to cultivate students who are tolerant, inclusive, and socially responsible. Although previous studies have emphasized formal religious instruction, the contribution of the hidden curriculum to fostering religious moderation remains underexplored. This study aims to examine how the hidden curriculum facilitates the internalization of religious moderation in an Indonesian madrasah. Using an interpretive qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, boarding school supervisors, and students. The data were analyzed through coding, categorization, interpretation, and triangulation to identify patterns of value internalization. The findings reveal that religious moderation is internalized through three interconnected stages: value transformation, value transaction, and value transinternalization. These stages are manifested through teacher role modelling, school culture, collective worship, boarding school life, and students' daily social interactions, fostering tolerance, mutual respect, responsibility, and inclusiveness. The study concludes that the hidden curriculum serves as a strategic mechanism for strengthening religious moderation by integrating moderate Islamic values into students' everyday educational experiences. These findings contribute to the discourse on Islamic education by demonstrating that the hidden curriculum provides a practical framework for promoting religious moderation in madrasahs.